Analisis Kemampuan Representasi Matematis Siswa SMK Ditinjau dari Gaya Belajar - Elsa Komala; Asri Maulani Afrida (Pendidikan Matematika STKIP Kusuma Negara, 2020)
This research aims to describe the mathematical representation abilities of vocational school students in terms of visual, auditory, and kinesthetic learning styles, as well as learning styles that have the best representational abilities in mathematics learning. The research was conducted at SMK Negeri 2 Cilaku Cianjur. The research method used is descriptive research with a quantitative approach. The subjects in this study were all 29 students of class X TKJ 2 with purposive sampling technique. The data used are written tests to reveal mathematical representation abilities, observation and questionnaires to classify students based on learning styles, interviews with students. Data processing used descriptive analysis of the percentage of posttest scores, learning styles by looking at the percentage of observation statements and answers to student questionnaire statements. The results of the data analysis showed that the percentage of achievement of the mathematical representation ability of students with a visual learning style was 71.43% in the sufficient category, students with the auditory learning style 71.25% in the sufficient category, and students with the kinesthetic learning style 73.89% with the sufficient category. The kinesthetic learning style has the best representation ability in mathematics learning with a percentage of 73.89% with a sufficient category.